Roux-en-Y gastrojejunal bypass using a hybrid NOTES-12mm trocar technique in a porcine model. Issue 2 (3rd March 2016) - Polese, Lino; Porzionato, Andrea; Luisetto, Roberto; Mastrogiacomo, Doralba; Macchi, Veronica; De Caro, Raffaele; Norberto, Lorenzo; Merigliano, Stefano
Abstract: Aims To evaluate the feasibility and safety of Roux-en-Y gastrojejunal bypass procedure using a hybrid NOTES-12 mm trocar technique in a survival porcine model.Material and methods The procedure was carried out on ten pigs. Two gastroscopes were introduced through the mouth and through a 12 mm trocar, respectively. A mechanical circular gastro-jejunal anastomosis was created by introducing a stapler after the trocar incision was enlarged. A 21 mm EEA OrVil circular stapler was utilized in the first six pigs and a 25 mm one was used in the other four. All pigs were fed beginning 24 hours after the procedure and were euthanized three weeks later.Results The procedure was successfully completed in all ten animals. The mean length of the skin incision was 2.5 cm. All pigs survived without complications. Endoscopic inspection detected anastomotic strictures in 5/6 of the 21 mm-stapler and in 0/4 of the 25 mm-stapler anastomoses ( p < 0.05). Conclusion Roux-en-Y gastrojejunal bypass using a hybrid NOTES-single 12 mm trocar access technique is a simple and safe procedure in a survival porcine model. Functional results need to be evaluated by further studies.